PROCESSES OF THE TELECOM OPERATOR’S INFORMATION ARCHITECTURE TRANSFORMATION - Leonid Smidovych; Yurii Davydovskyi (Сучасний стан наукових досліджень та технологій в промисловості, 2022)
The subject of the article is the architecture of information systems of telecom operators (BSS/OSS), requirements for it and the processes of its transformation. The goal is to transform the existing information environment of the operator into an open digital ecosystem, in accordance with business and technological requirements for the functionality and architecture of information systems of communication operators, which will introduce new business models, services and products, communication channels, and increase competitiveness. The following tasks were solved at the study: analysis of the current state of telecommunications and information systems used by telecom operators; analysis of requirements for business support and operational information systems, collection and analysis of requirements for the architecture of modern information systems in the field of telecommunications, analysis of the transformation process from the existing BSS/OSS architecture of the communication operator into the target architecture of the digital communications provider, elaboration of a recommendations for an intermediate architecture. To solve these problems, methods of system and business analysis were used, in particular, methods of analysis of software requirements, technologies for developing software application architecture. The following results were obtained. The current state of the telecommunications services industry, the features of the existing information systems of telecommunications operators (BSS/OSS) and the requirements for the architecture of such systems was analyzed. Strategies of transition to modern architecture was considered and analyzed. The target architecture of the digital service provider's information ecosystem and the process of transforming the existing BSS/OSS architecture into the target architecture were considered. Intermediate migration architecture was proposed. Conclusions: the transformation to modern information architecture will ensure compliance of BSS/OSS systems with market requirements and new technologies, adapt to their changes, allow operators to increase competitiveness, reduce operating and capital costs, create technological conditions for open digital ecosystem and transform the operator into a digital services provider. It was recommended to use an intermediate architecture based on the open standardized TMF API for such transformation.